Pengaruh Green Financing terhadap Financial Distress - Amylia Haryati; Sri Fadilah (UNISBA Press, 2024)
Abstract. Bankruptcy in companies, especially banks, will usually begin with an unhealthy bank condition characterized by financial difficulties. To reduce credit risk, the bank may increase its loan portfolio by channeling green financing because green financing is a less risky financing. So, the problem in this study is defined as follows,